Media choice: "Traditional media", "Online Pic' n' mix" & "Sponsorship" - Hagen, Dan; Matthews, Kieron; Mason, Rob (Henry Stewart Talks, 2010)
Traditional media: What is traditional media?, Key drivers of media change, The rules of media planning are changing, Changes in consumer behavior and expectation, Smart brands are connecting in multiple ways, Understanding consumers better, The benefits of different media channels Online Pic' n' mix: The market has changed dramatically, Disappearance of high street shops, Shoppers have moved online, The first recession since the internet has become a mass medium, Online is the only medium showing growth, The digital media mix, Trends in: participation, advocacy, contribution, diversity and innovation Sponsorship: The rapidly changing media landscape, along with more sophisticated consumers, has allowed sponsorship to become one of the most powerful routes to engage audiences, Definition of sponsorship, Understanding, buying and activating it, Case histories, Sponsorship is 'content' which feeds other marcoms channels as opposed to the more common brand marketers view that sponsorship is a channel in itself